E-Marketplace Development With C2C Model And Appreciative Inquiry - Bambang Agus Herlambang; Muhammad Saifuddin Zuhri; Dwi Nuvitalia (Jurusan Teknologi Informasi Universitas Semarang, 2018)
People's lifestyles change in spending their funds have changed. Trend of software development innovation in Indonesia could be mapped into several types of E-Commerce, Media, Transportation, Accommodation and Logistics and Education. Now, there are 45 young entrepreneurs at the University PGRI Semarang. They need a tool to maximize business transactions, so it is necessary to develop E-Marketplace. The E-Marketplace Application System will be integrated with the Apprecitive Inquiry concept to reward users who frequently perform activities on the E-Marketplace application system. UML (Unifield Modeling Language) was used as a tool in designing this system. The result of this research is E-Marketplace application system that can run on web and mobile (hybrid) platform so it is expected to be a new marketing tool for young entrepreneurs at UPGRIS.